1998
DOI: 10.1007/bf02290934
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrogenation of pyrylium salts

Abstract: On catalytic reduction of 2,6-diphenylpyrylium salts, hydrogenolysis occurs at the C-O bond with the formation of 1,5-diphenylpentanes. The principal direction of the hydrogenation of 9-phenyl-symoctahydroxanthylium tetrafluoroborate is the formation of a mixture of products of partial and complete reduction of the heterocycle. The structure of the substances obtained was established by IR and 13C NMR spectroscopy.Catalytic hydrogenation is a practically uninvestigated aspect of the well-studied chemistry of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…We have previously shown that by the catalytic (Pd/C) hydrogenation of pyrylium salts bearing 2,6-dialkyl-substituents ( 1 ) one may conviently obtain, in preparatively useful yields, the correspondingly substituted all -cis -tetrahydropyrans 2 . , If the initial pyrylium salt has 2,6-diaryl substituents , or is polycyclic, the hydrogenation is less chemoselective leading to complicated mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that by the catalytic (Pd/C) hydrogenation of pyrylium salts bearing 2,6-dialkyl-substituents ( 1 ) one may conviently obtain, in preparatively useful yields, the correspondingly substituted all -cis -tetrahydropyrans 2 . , If the initial pyrylium salt has 2,6-diaryl substituents , or is polycyclic, the hydrogenation is less chemoselective leading to complicated mixtures.…”
Section: Introductionmentioning
confidence: 99%